Epicardial adipose tissue volume is not an independent predictor of atrial fibrillation recurrence after ablation - Inês Maria Amorim Cruz (2022)
Aims: Previous studies have suggested that epicardial adipose tissue (EAT) could exert a paracrine effect in the myocardium. Indeed, few earlier studies have assessed the role of EAT in the risk of atrial fibrillation (AF). This study aimed to evaluate the association between EAT volume and its attenuation with the risk of AF recurrence after catheter ablation. Methods and Results: 350 consecutive patients submitted to AF ablation (2017-2019) were included in this cohort study - 34% female, median age 57 years (IQR 48-65), 21% with persistent AF. Fat was measured by the automatic calculation of pericardial fat volume (PATV) and by the evaluation of EAT volume through manual tracing of the pericardium (EATV) using Syngo.via Frontier-Cardiac Risk Assessment software. The attenuation of EAT (which could be a marker of local inflammation) was also assessed by manually contouring an area of fat between left atrium and esophagus. The primary outcome was AF recurrence, defined as any documented episode of AF, atrial flutter, or atrial tachycardia, more than 3 months after procedure. After a median follow-up of 34 months (range 12 to 57 months), 114 patients (33%) had AF recurrence. We observed that patients with an EATV ≥ 80 mL had an increased risk of AF recurrence in the univariable Cox regression [HR 1.65 (95% CI 1.14-2.39), p = 0.007]. However, after multivariable adjustment, EATV did not remain an independent predictor of AF recurrence [HR 1.24 (95% CI 0.83-1.87, p = 0.3)]. Similar results were observed with PATV. Moreover, patients with lower attenuation of EAT did not have a higher risk of recurrence (log-rank test p = 0.75). Conclusion: EAT parameters including the evaluation of EATV, PATV and EAT attenuation were not independent predictors of AF recurrence after catheter ablation.